#TITLE_ALTERNATIVE# - Nurjaman (NIM 150 03 067) Faisal Kasanofa (NIM 150 03 097) , Ahmad
Abstract: Column is a structural element of building that receives axial and flexural load. Damage or under designed column require upgrading to enhance axial load capacity and flexural capacity. FRP is a new composite material for strengthening method that should be considered as an alternative, because of its light weight and high tensile strength so that the application and installation of FRP material jacketing is easier than the other strengthening methods This final report will discuss confinement effect contributed by FRP involved with compressive and shear strength in circular and rectangular column cross section. Some experimental database have been collected with various test variables such as effect of columns diameter, column compressive strength and the thickness of FRP layers. In the case of analysis compressive strength, there are 4 interaction diagrams that have been created. The first diagram uses the compressive strength of unconfined concrete in its computation, whereas the second one uses the compressive strength of confined concrete with transversal bars and the third one uses FRP-confined compressive strength, where only the tensile portion of FRP is taken in to account. The last one is interaction diagram for FRP jacketing that considered all part of FRP, i.e., the tensile and the compressive ones. But compressive strength of FRP is taken as 78percent from the tensile strength. While in the case of shear strength will be evaluated the improvement of shear strength as result FRP contribution.